Carruthers and Constitutive Self-Knowledge - Hill, John C. (Stance: an international undergraduate philosophy journal, 2013)
In his recent book, The Opacity of Mind, Peter Carruthers advances a skeptical theory of self-knowledge, integrating results from experimental psychology and cognitive science.1 In this essay, I want to suggest that the situation is not quite as dire as Carruthers makes it out to be. I respond to Carruthers by advancing a constitutive theory of self-knowledge. I argue that self-knowledge, so understood, is not only compatible with the empirical research that Carruthers utilizes, but also helps to make sense of these results.